2020
DOI: 10.1111/ijfs.14848
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of arabinoxylan and (1,3)(1,4)‐β‐glucan alternating multilayer edible films simulated those of wheat grain aleurone cell wall

Abstract: Various observations show a lamellar organisation of wheat aleurone cell walls, that likely acted as barriers to regulate the water diffusion rate in wheat grains. In this study, arabinoxylan (AX) and (1,3)(1,4)-βglucan (BG) alternating multilayer films which mimic cell wall of aleurone structure were prepared. Twenty layers of alternating multilayer films of AX/BG were prepared with individual thicknesses of 20 µm. The water diffusion and water mobility of the films were determined using dynamic vapour sorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Wheat bran AXs are consisted of a linear backbone of β-(1 → 4)-linked D-xylopyranosyl (Xylp) units with α-Larabinofuranosyl substituents (Araf) attached to the O-3 and/or O-2 positions of the Xylp residues (Rudjito et al, 2019;Ying et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat bran AXs are consisted of a linear backbone of β-(1 → 4)-linked D-xylopyranosyl (Xylp) units with α-Larabinofuranosyl substituents (Araf) attached to the O-3 and/or O-2 positions of the Xylp residues (Rudjito et al, 2019;Ying et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat bran AXs are consisted of a linear backbone of β‐(1 → 4)‐linked D‐xylopyranosyl (Xyl p ) units with α‐L‐arabinofuranosyl substituents (Ara f ) attached to the O‐3 and/or O‐2 positions of the Xyl p residues (Rudjito et al, 2019; Ying et al, 2021). The extracted AXs could be divided into water extractable arabinoxylan (WEAX) and water unextractable arabinoxylan (WUAX) (Kaur et al, 2019; Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the values of W 1 and W 2 increased, while the values of W 3 decreased (Table 3). This indicated that the content of the aleurone‐rich fraction increased, the mobility of water molecules in the bread decreased (Ying et al., 2020b), and the proportion of bound water increased (Guo et al ., 2018). In addition, arabinoxylans and β‐glucans in aleurone have strong water‐binding properties (Hemdane et al ., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, crop wastes such as rye flour, oats, and arabinoxylan in wheat bran have been studied extensively with the objective of preparing film materials [ 2 ]. In addition, arabinoxylan extracted from wheat flour has been used to prepare edible films [ 3 ].…”
Section: Introductionmentioning
confidence: 99%